Global Assets Mitigate Global Inflation - Bechtel, Gordon (Advances in Social Sciences Research Journal, 2022)
This article finds that 26 global assets mitigate global inflation. Fractional polynomial regressions return sizable goodness-of-fit R2s for these assets, along with high mitigating Pearson correlations between these assets and global inflation. It is hoped that future fractional polynomial regressions will reveal other global assets that also mitigate global inflation. In view of Russia’s invasion of the Ukraine, which preempted American President Biden’s State of the Union address (Aljazeera, March 1 2022), and the trade war between the United States and China, the United Nations has now stepped in to protect it’s member states from the interest-rate and inflationarity effects wrought by these three super powers.